Nanocapsules of oregano essential oil preparation and characterization and its fungistasis on apricot fruit during shelf life. Issue 7 (31st May 2021) - Shi, Zedong; Jiang, Yaping; Sun, Yingjie; Min, Dedong; Li, Fujun; Li, Xiaoan; Zhang, Xinhua
Abstract: Oregano essential oil nanocapsules (OEO‐NPs) were successfully prepared via a complex coacervation method. The results of this study showed that the percentage encapsulation of the OEO‐NPs prepared by the best technological process was 88.3%, the loading amount of oregano essential oil (OEO) was 74.36%, and the average particle size was 135 nm. OEO‐NPs exhibited better spherical and regular surface structure, higher thermal stability, and slow‐release performance. In addition, the 4% OEO‐NPs showed better fungistatic effect and reduced decay rate, which compared with the control, 2% and 8% OEO‐NPs treatments, during apricot shelf life; 4% OEO‐NPs also increased peroxidase, L‐phenylalanine ammonialyase, β‐1, 3‐glucanase, catalase and chitinase activities, while reduced the polyphenol oxidase activities during fruit shelf life than that in control. These results provided a new idea for the development of a slow‐release fungistatic agent based on plant essential oils. Novelty impact statement: Oregano essential oil nanocapsules (OEO‐NPs) possessed higher thermal stability and slow‐release performance. 4% OEO‐NPs showed a better fungistatic effect and reduced apricot fruit decay rate during shelf life. OEO‐NPs provided a new idea for the development of green and slow‐release fungistatic agent.